ANALYZING STUDENTS’ GRAMMATICAL ERRORS IN WRITING NARRATIVE TEXT AT SECOND SEMESTER STUDENTS OF UNISMA - Nona Asfiyati (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
This study aimed to find out the types of grammatical errors made by the second semester students of UNISMA in writing narrative text, to describe the most common grammatical error made by the second semester students of UNISMA in writing narrative text and to find out the causes of grammatical errors produced by the second semester students in their narrative text. This study employed descriptive qualitative. The population of the study was second semester students of English Education Department of Teacher Training and Education Faculty of University of Islam Malang in academic year 2020/2021. The researcher chose ten papers of students’ personal narrative. The findings showed that the second semester students made errors in all types of surface strategy taxonomy namely omission (20 or 20.8%), additions (16 or 16.6%), misformation (56 or 58.3%) and misordering (4 or 4.16). The most common grammatical error made by the students was misformation with 56 or 58.3% errors and the causes of students’ grammatical errors were interlingual and intralingual transfer. Hence it could be concluded that the students’ understanding towards English grammar was still low, they found difficult to construct a sentence with the proper form of morpheme and structure, and they were still influenced by their mother tongue and had lack of knowledge about the target language.